Exploring the Therapeutic Potential of Natural Compounds and Plant Extracts in Human Health - Laura Zeppa; Cristina Aguzzi; Maria Beatrice Morelli (Biomolecules, 2025)
A growing body of evidence supports the various potential advantages of plant extracts and plant extract-based products in promoting human health and addressing a broad range of pathological conditions [...]